DETERMINATION OF POTENTIAL LOCATIONS FOR RELOCATION OF STREET VENDORS STREET VENDORS IN GRESIK URBAN AREA - Afifah, Wanda Rifatul; Surjono, Surjono; Hasyim, Abdul Wahid (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2025)
Street vendors are one of the informal trade and services sectors that grow to meet economic needs. The urban economic dynamics of street vendors' existence invite various problems, such as utilising strategic public spaces that should not be used for selling. Six of the eight street vendor locations in the Gresik Urban Area are scattered, occupying road corridors, sidewalks, and public open spaces. This study aims to determine potential locations for relocating street vendors in the Gresik Urban Area. The spatial autocorrelation analysis method used is LISA (Local Indicator of Spatial Association) analysis. X variables include the location of residential land use, offices, tourism, and industry, which are compared with the location of street vendors as variable Y. Based on LISA analysis, the location used as a relocation recommendation is in the high-high quadrant and has a positive correlation. The results of the LISA analysis overlay between Settlement-Street vendors, Office-Street vendors, Tourism-Street vendors, and Industry-Street vendors revealed that the variables for Settlement-Street vendors and Tourism-Street vendors exhibit a positive spatial correlation. Thus, potential locations for relocating street vendors in the Gresik Urban Area are Randuagung Village and Gapurosukolilo Village.